Process Types of Transitivity System in Engineering Lecture Introduction: A Pedagogic Discourse - Heri Kuswoyo; Akhyar Rido (LINGUA: Jurnal Bahasa dan Sastra, 2019)
Abstract: This study is aimed at investigating the transitivity process types constructed in a pedagogical discourse of engineering lecture introduction in a university in the Netherlands, where English is used as the medium of instruction. The pedagogic discourse theory and tran- sitivity analysis were employed to analyze the data. A qualitative approach was applied in this study while the data were collected from Cosmolearning Corpus’s 7 engineering lectures. The findings showed that all transitivity processes appeared in engineering lecture introduction. Material process, relational process, mental process, verbal process, behavioral process, and existential process were identified. It was also revealed that the most dominant process used by the lecturers in engineering lecture was material process. This indicated that the engineering lecturers in lecture introduction have succeeded at reaching the level of material process. In oth- er words, they were aware of realization aspect of the students’ behavior because all of them di- rected toward the goals of the teaching-learning activity. To sum up, at the engineering lectures introduction, the regulative register which was related to the goals, purposes, and directions of the teaching-learning activity became very important. Keywords: process types of transitivity system, engineering lecture, pedagogic discourse, sys- temic functional linguistics Abstrak: Penelitian ini bertujuan untuk menyelidiki jenis proses transitivitas yang dibangun dalam wacana pedagogis perkuliahan pembuka kelas teknik di satu universitas di Belanda yang menggunakan bahasa Inggris sebagai bahasa pengantar. Teori wacana pedagogis dan analisisis transitivitas digunakan untuk menganalisis data. Pendekatan kualitatif diterapkan pada pene- litian ini sedangkan data diambil dari 7 sesi perkuliahan teknik di TU Delft, Belanda pada Korpus Cosmolearning. Temuan menunjukkan bahwa semua proses transitivitas muncul dalam perkuliahan pembuka kelas teknik. Proses material, proses relasional, proses mental, proses verbal, proses perilaku, dan proses eksistensial teridentifikasi. Temuan juga mengungkapkan bahwa proses yang paling dominan digunakan oleh dosen dalam perkuliahan pembuka kelas teknik adalah proses material. Ini menunjukkan bahwa perkuliahan pembuka kelas teknik telah berhasil mencapai tingkat proses material. Dengan kata lain, dosen menyadari aspek realisa- si dari perilaku mahasiswa karena itu semuanya menunjukan tujuan langsung dari kegiatan belajar-mengajar. Sebagai kesimpulan, dalam perkuliahan pembuka kelas teknik, regulative register yang berkaitan dengan target, tujuan dan arah dari kegiatan pengajaran-pembelajaran menjadi hal yang sangat penting. Kata- kata Kunci: jenis proses sistem transitivitas, perkuliahan teknik, wacana pedagogis, linguistik sistemik fungsional